Genetic Polymorphisms New Insights - Çalışkan, Mahmut (IntechOpen, 2022)
This book provides a glimpse into the dynamic process of genetic polymorphism by presenting studies carried out on different kinds of organisms at the DNA level or gene expression level. Chapters address such topics as genetic polymorphism in animals, gametocyte biomarkers, thrombotic disorders, prostate cancer, and more.